THE FUTURE OF ARTIFICIAL INTELLIGENCE IN BUSINESS - Omar Ashurbaev (Web of Journals Publishing, 2024)
Artificial Intelligence (AI) is a transformative technology of bottom-line importance to business, providing revolutionary solutions, while it is redefining the new problems. This literature review explores the role of AI in buisness by addressing three critcal questions: what challenges buisnesses have with AI, what problems AI solves for buisnesses, and buisnesses potential in the future of AI.